Management aspects in the short story Cikgu Tapa (2013) by Nurul Afna Akma Zakaria - Sujud, Arbaie; Nik Hamdan, Nik Nurul Syahirah; Nik Muhamad Affendi, Nik Rafidah; Md Zain, Rosnani; Mohamad, Zulkifli (Human Resource Management Academic Research Society, 2022)
This study was conducted to examine the management aspects in the short story Tapa (2013) by Nurul Afna Akma Zakaria. This study is based on the importance of management in life. The objective of this study is to classify the management elements in the short story Cikgu Tapa (2013) by Nurul Afna Akma Zakaria. Next, analyze and summarize the management aspects found in the short story (Tapa, 2013). Management Approach in Literary Criticism by Mohamad Mokhtar Abu Hassan was used to examine the short story. This study found that the short story Tapa (2013) by Nurul Afna Akma Zakaria showed management in everyday life. This management can be seen through elements such as planning, organizing, leadership, staffing (workforce), and control displayed through the characters found in the short story.